A monotone iterative method for boundary value problems of parametric differential equations. (2001) - Liu, Xinzhi; McRae, Farzana A.
Abstract : This paper studies boundary value problems for parametric differential equations. By using the method of upper and lower solutions, monotone sequences are constructed and proved to converge to the extremal solutions of the boundary value problem.